Development and Validation of Stability-indicating UPLC Method for the Simultaneous ESTIMATION of Voxilaprevir, Sofosbuvir, and Velpatasvir in Formulations (Asian Journal of Pharmaceutics (AJP), 2020)
Aim: The aim of the present research work was to develop a sensitive, rapid and accurate, stability-indicatingRP-UPLC method for the simultaneous estimation of voxilaprevir (VXR), sofosbuvir (SFR), and velpatasvir(VLR) in formulations. Materials and Methods: The chromatographic separation of mixture of VXR, SFR, andVLR was attained in isocratic method utilizing a mobile phase of 0.01N potassium dihydrogen orthophosphate(pH 4.8) and methanol in the proportion of 50:50% v/v utilizing a CHS C18 column which has dimensions of100 Ã— 2.1 mm, 2.0 m particle size and the flow rate of 1.0 mL/min. The detection system was monitored at 260 nmwavelength maximum with 1.0 mL injection volume. Results: The retaining time for VXR, SFR, and VLR wasachieved at 1.468 min, 0.606 min, and 0.848 min, respectively. VXR, SFR, and VLR and their combined drugformulation were exposed to thermal, acidic, oxidative, photolytic, and alkaline conditions. The present methodwas validated as per the guidelines given by the ICH for specificity, accuracy, sensitivity, linearity, and precision.Conclusion: The developed method was highly sensitive, rapid, precise, and accurate than the earlier reportedmethods. The total run time was decreased to 3.0 min; hence, the technique was more precise and economical.Stability studies directed for the suitability of the technique for degradation studies of VXR, SFR, and VLR. Theprojected method can be utilized for routine analysis in quality control department in pharmaceutical trades.